Determination of Minimum Inhibitory Concentration (MIC) of Hygromycin B in CHO cells: The minimum inhibitory concentration determination - Naddafi, Fatemeh; Tabarzad, Maryam; H. Shirazi, Farshad (Iranian Journal of Pharmaceutical Sciences, 2019)
Chinese hamster ovary (CHO) cells are considered as the most commonly used host for industrial manufacturing of therapeutic proteins. The aim of this study was to evaluate the minimum inhibitory concentration (MIC) of hygromycin B in both CHO-DG44 and CHO-S cells since hygromycin B resistance cassette can be used for future selection of gene expression in CHO cells. The minimum inhibitory concentration was determined by the microdilution method. In this test, CHO cells were subjected to a range of hygromycin B concentrations for a defined period of time. Moreover, CHO cells were scaled up with no addition of fresh culture medium during the growth–culture cycle to investigate their growth. The MIC for hygromycin B in CHO-DG44 cells was 75 μg/ml and for CHO-S cells was 50 μg/ml. Thus, it has been indicated that CHO DG44 cell line could be more effective for stable cell line development than CHO-S cell line.